Estimation of single-dose varicella vaccine effectiveness in South Korea using mathematical modeling - Jiyeon Suh; Jae-Ki Choi; Jeehyun Lee; Sun Hee Park (Taylor & Francis Group, 2022)
In South Korea, despite the implementation of a universal single-dose vaccination program for children aged 12-15 months in 2005, the varicella incidence rate remains significant. Prior case-control studies have reported that currently used varicella vaccines are extremely inefficacious. We estimated vaccine effectiveness (VE) by fitting a dynamic transmission model to age-specific varicella incidence data from 2007 to 2015 and available vaccine coverage data. The initial vaccine efficacy and primary failure rates were estimated to be 61.1% and 38.9%, respectively. The average duration of protection was 21.4 years. The mean VE [(1-relative risk) %] for the simulated data of 2004-2014 birth cohorts decreased from 59.8% to 50.7% over 9 years. This mathematical modeling study demonstrated that the single-dose vaccine exhibits moderate effectiveness, and a high proportion of primary failure could be a main cause of breakthrough infections. Therefore, a two-dose vaccination strategy should be considered.